The Correlation of the Parts of Speech Mastery and Students’ Writing Descriptive Text Ability - Linda Efrina nasution; Astriadi Buaya; Ahmad Ripai Rangkuty (Journal of Information System and Education Development, 2024)
The objectives of this research is to find out wheter there is a significant correlation between part of speech and student ability in writing descriptive text. Tenth grade students of SMA Negeri 1 Ulu Barumun are the population, which is consisted of 160 students and the sample was taken by cluster sampling that consist of 54 students. This script is carried by using experimental method. The instrument used for collecting the data is test. After collecting the data, it was analyzed by using Pearson Product Moment. after analyzing the data, it can be concluded that there is a significant correlation between part of speech and student ability in writing descriptive text at the grade tenth students of SMA Negeri 1 Ulu Barumun and categorized very good. By using the statistical analysis, based in the table of “r” value at the degree of significance of 5% with df 52, it is found that the value of 5 % of degree of significance is 0.266. The result is robserver is higher than rtable (0.67 > 0.266). It is found that the value of coefficient of Determination is 45 %, means the parts of speech is affected students’ writing ability as much as 45%. It can be concluded that the alternative hypothesis of this research is accepted Keyword : Part of Speech, Descriptive text, writing.